Corporate governance and corporate performance of shariah compliant companies in Malaysia and Singapore: Examining from an Islamic perspective - Lee, Sin Yee (2019)
The objective of this research is to indicate corporate governance contribution to the Shariah- compliant companies’ performance in Malaysia and Singapore from an Islamic perspective. Corporate governance variables as the independent variables applied in this research are number of Muslim directors, number of nonMuslim directors, board size, Muslim CEO, number of Muslim independent directors, Muslim Chairman and number of directors holding professional Accounting qualification. Return on Assets (ROA), Return on Equity (ROE) and Tobin’s Q are the dependent variables that represent the company performance. The sample frame are 30 companies from FTSE Bursa Malaysia Hijrah Shariah Index and 30 companies from FTSE ST Singapore Shariah Index. The research time frame included from year 2013 to 2018. Panel Data Analysis was applied to determine the results of overall 6 years period. Hausman Test was adopted to determine whether Fixed Effect Model or Random Effect Model is the most appropriate model to be used in the research. Furthermore, Multiple Linear Regression was performed as an additional analysis. The findings of this research presented NOMID has significant influence on ROA in Malaysia and Singapore. NODHPAQ also has significant influence on ROA in Singapore but not in Malaysia. Meanwhile, all the others independent variables such as NOMD, NONMD, BS, MCEO and MC have no influence on ROA, ROE and Tobin’s Q in Malaysia and Singapore.